System of collective funds as a strategy for the acquisition of assets of Tacna companies in 2016 - Vargas Monroy, Joanette Ivette (2018)
This research work brings together the different aspects related to the Collective Funds System as a strategy for the acquisition of assets from the Tacna companies in 2016, as well as the Collective Funds System is a form of financing that time has been acquiring greater relevance as an option for the acquisition of assets. It is non-experimental, descriptive and correlational. The companies financed with collective funds from the city of Tacna have been considered as a population, as a technique a survey has been used and as a tool a questionnaire was used to evaluate the variables under study. The research area is framed in Financial Accounting. The Collective Funds Management Companies have been an alternative financing for the acquisition of assets for the Tacna companies, allowing to improve their income and therefore the economic and financial growth of each of these companies, allowing them to improve their profitability and therefore their economic development, giving thousands of people the opportunity to access better levels and quality of life.